Pelatihan terhadap Pemahaman Materi Konseling Kelompok dengan Pendekatan Realitas pada Guru Bimbingan dan Konseling - Manora, Elsa; Sofah, Rahmi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
This study aims to determine the effect of group counseling training on the understanding of Guidance and Counseling Teachers. The research method used is an experimental method with a pre-experimental design of One Group Pretest-Posttest Design. The research subjects of this research were guidance and counseling teachers who participated in group counseling training using a reality approach to community service lecturers of guidance and counseling study program. The number is 30 people consisting of 16 guidance and counseling teachers for SMP/MTs, and 14 SMA/SMK in Indralaya Ogan Ilir. Data collection techniques using test techniques. The test wasgiven before treatment and after treatment. The data analysis technique used is the ttest (paired sample T test). The results of the study mean the pretest score is 14.5 and the standard deviation is 4.0, while the average score for the post-test is 17.9 with a standard deviation of 4.3. The results of the t test obtained t count = -6.89. The result of the t-test obtained is 6.89, which is greater than the t-table 2.04 with 0.00 < 0.05 in a significant level of 5%. This shows that there is an effect of training on understanding group counseling materials for guidance and counseling teachers.